2006
DOI: 10.1007/s11094-006-0127-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiarrhythmic properties of N-acylamino derivatives of 1,6,7-substituted 1,2,3,4-tetrahydroisoquinoline-4-spirocyclopentanes and their analogs

Abstract: A series of new N-chloracetyl derivatives have been synthesized proceeding from 4-spirocyclopentane-substituted 1,2,3,4-tetrahydroisoquinolines, 1-phenyl-1-cyclopentylmethylamine, and chloroanhydrides of bromoacetic and a-bromopropionic acids. Reactions of these bromoamides with amines (piperidine, morpholine) yield the title N-acylamino derivatives. The antiarrhythmic properties of the synthesized compounds have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that lyotropic liquid crystals are typical representatives of biological membranes, and the validity of using the latter as models for DOI:10.54503/18291171-2022.15.2-3-67 the organization of biomembranes has been proven [13][14][15][16]. One of the approaches to the study of such problems was developed in the works of Markaryan S.A. and others, where surfactants were used that form reverse micelles in water [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that lyotropic liquid crystals are typical representatives of biological membranes, and the validity of using the latter as models for DOI:10.54503/18291171-2022.15.2-3-67 the organization of biomembranes has been proven [13][14][15][16]. One of the approaches to the study of such problems was developed in the works of Markaryan S.A. and others, where surfactants were used that form reverse micelles in water [17][18][19].…”
Section: Introductionmentioning
confidence: 99%